2023
DOI: 10.1111/joim.13639
|View full text |Cite
|
Sign up to set email alerts
|

Low‐carbohydrate diets, low‐fat diets, and mortality in middle‐aged and older people: A prospective cohort study

Abstract: al. Low-carbohydrate diets, low-fat diets, and mortality in middle-aged and older people: A prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
(69 reference statements)
1
10
1
Order By: Relevance
“…In the current issue of the Journal of Internal Medicine, Zhao et al provided new evidence supporting the importance of diet quality in preventing premature deaths, as shown in a large US population of ∼371,000 men and women aged 50-71 years, followed for ∼23 years [6]. Carbohydrate and fat qualities are known to be a key determinant of health outcomes, but in this prospective study, it is shown in the context of both low and high carbohydrate intake.…”
Section: Diet Quality and Mortality: Epidemiological Lessons For Prev...mentioning
confidence: 69%
See 4 more Smart Citations
“…In the current issue of the Journal of Internal Medicine, Zhao et al provided new evidence supporting the importance of diet quality in preventing premature deaths, as shown in a large US population of ∼371,000 men and women aged 50-71 years, followed for ∼23 years [6]. Carbohydrate and fat qualities are known to be a key determinant of health outcomes, but in this prospective study, it is shown in the context of both low and high carbohydrate intake.…”
Section: Diet Quality and Mortality: Epidemiological Lessons For Prev...mentioning
confidence: 69%
“…The LCD and LFD dietary patterns were defined as "healthy" or "unhealthy" based on a dietary quality score (e.g., taking into account different types of carbohydrate rich-foods, saturated and unsaturated fats, and plant or animal based protein). Overall, the results suggest more favorable associations between LFD and LCD and mortality at healthier versions of both these dietary patterns [6]. Thus, higher quality of both diets was a consistent determinant of better survival.…”
Section: Diet Quality and Mortality: Epidemiological Lessons For Prev...mentioning
confidence: 71%
See 3 more Smart Citations